Rational choice and political imaging in mining areas: a case study of legislative elections in East Luwu - Muhammad, Rahmat; Syam, Ridwan; Yahya, Irfan; Asis, Patta Hindi (Frontiers in Sociology, 2025)
The 2024 legislative elections in Indonesia present an important opportunity to examine the dynamics of voters’ rational choices in the context of developing democracy. This study investigates differences in voters’ rational choices regarding the image-building actions of legislative candidates in the East Luwu mining industry, focusing on the differences between inner and outer mining circles. Using a qualitative approach with in-depth interviews of ten key informants, this research reveals significant variations in voter rationality and their responses to candidates’ image-building strategies. The findings indicate that voters within the inner mining circle exhibit greater rationality and critical thinking in their decision-making. They tend to evaluate candidates based on their track records, policy proposals, and overall competence—reflecting a more educated, policy-focused, and socially conscious electorate with high social capital. Conversely, in the outer mining circle, voters are influenced more by primordial factors and short-term incentives, so this is driven by kinship, short-term incentives, low info access, and traditional loyalties. In terms of differences in education, access to information, campaign methods, and voter priorities as indicators of voters. Nevertheless, the roles of social capital and social networks remained significant in both areas. These differences reflect variations in education level, welfare, and access to information. This study contributes to the development of rational choice theory by demonstrating how structural factors can influence political rationality at the local level. Important implications include the need for different campaign strategies and political education efforts that consider specific characteristics of local communities.